Response of Coleus aromaticus to Glomus fasciculatum and other beneficial soil microflora - Bagyaraj, C K Suresh, N Earanna, R R Mallikarjuniah, D J (Journal of Spices and Aromatic Crops, 2001)
Stem cuttings of Coleus aromaticus were treated with vesicular arbuscular mycorrhiza (Glomus fasciculatum) and beneficial microorganisms viz., Bacillus coagulans, Pseudomonas fluorescens, Azotobacter chroococcum and Trichoderma harzianum either singly or in combination of organisms. The number of leaves and branches; total biomass, nitrogen and phosphorus contents were higher in plants treated with G. fasciculatum alone. Synergistic effect was noticed especially in plants treated with G. fasciculatum + P. fluorescens. Mycorrhizal colonization in roots was also maximum when V AM was applied alone.